Exploring The Mudharabah Contract And Its Implementation In Islamic Financial Institutions: A Content Analysis Study In The Digital Entrepreneur Era - Syakur, Abd.; Chandrarin, Grahita; Wikantiyoso, Respati; Sunardi, Sunardi (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The application of mudharabah contract accounting practices has complied with accounting principles in Indonesian Islamic banking, as outlined in Financial Accounting Standards Statement (PSAK) No. 105, issued by the Indonesian Institute of Accountants, which addresses measurement and recognition, presentation, and disclosure. Myriad studies have examined the current development of Islamic accounting discourse; however, theoretical discussions have been somewhat overlooked. To fill this lacuna, the current study explicitly explores Islamic accounting practices for mudharabah contracts in Islamic banking financing. The study aims to uncover Islamic accounting practices for mudharabah contracts in Islamic banking and to determine whether the implementation of these practices in financing aligns with the Statement of Financial Accounting Standards (PSAK) Number 105 and the Fatwa of the National Sharia Council. The current study employed a content analysis study under the umbrella of descriptive qualitative analysis to describe the practice of implementing Sharia accounting for mudharabah contracts in Islamic financing and financial institutions, based on compliance with PSAK No. 105. Furthermore, the study untangled that Islamic banking is considered a solution to conventional banking (which relies on interest). Although mudharabah is more commonly known in Islamic banking, it can also be applied in practice to other Islamic financial institutions, such as Islamic insurance, Islamic capital markets, Islamic mutual funds, and Islamic bonds.